Estrutura a termo da taxa de juros no Brasil e previsibilidade de ciclos econômicos - Ribeiro, Priscila Fernandes (2010)
This work proposes characterize Yield Curve for Brazil by three factors, comparing two types of estimation methods: using State Space model, estimate it by Kalman Filter and Two Steps Least Squares. The factors are the dynamics represented by a Vector Autoregressive model, VAR (1), and the second estimation method is attributed a structure for the conditional variance. To compare the methods used, it is proposed an alternative way of comparison: using Markov processes, an econometric model of the joint dynamic relationship between the slope of yield curve and the economy to predict business cycles.